Construction of pseudorabies virus variant attenuated vaccine: codon deoptimization of US3 and UL56 genes based on PRV gE/TK deletion strain - Xu, Mengwei; Zhu, Laixu; Ge, Aimin; Liu, Yamei; Chen, Saisai; Wei, Ziwen; Zheng, Yating; Tong, Ling; Wang, Zhisheng; Fei, Rongmei; Wang, Jichun; Zhang, Chuanjian (Frontiers in Microbiology, 2023)
Since 2011, pseudorabies based on the pseudorabies virus (PRV) variant has emerged as a serious health issue in pig farms in China. The PRV gE/TK or gE/gI/TK deletion strains protect against emerging PRV variants. However, these variants may cause lethal infection for newborn piglets without PRV antibodies. Previous studies have shown that codon deoptimization of virulence gene causes virus attenuation. Accordingly, we deoptimized US3-S (US3 gene encoding short isoform that represents about 95% of the total US3 transcription) and UL56 gene (first ten or all codons) of PRV gE/TK deletion strain (PRVΔTK&gE-AH02) to generate six recombinant PRVs through bacterial artificial chromosome technology. In the swine testicular cells, recombinant PRVs with all codons deoptimization of US3-S or UL56 genes were grown to lower titers than the parental virus. Notably, US3-S or UL56 with all codons deoptimization reduced mRNA and protein expressions. Subsequently, the safety and immunogenicity of recombinant PRVs with codon deoptimization of US3-S or UL56 are evaluated as a vaccine candidate in mice and piglets. The mice inoculated with recombinant PRVs with codon deoptimization of US3-S or UL56 showed exceptional survival ability without severe clinical signs. All codons deoptimized US3-S and UL56 significantly decreased virus load and attenuated pathological changes in the brain of the mice. Moreover, the protection efficiency offered by recombinant PRVs with codon deoptimization of US3-S or UL56 showed similar effects to PRVΔTK&gE-AH02. Remarkably, the 1-day-old PRV antibody-negative piglets inoculated with PRVΔTK&gE-US3-ST-CD (a recombinant PRV with all codons deoptimization of US3-S) presented no abnormal clinical symptoms, including fever. The piglets inoculated with PRVΔTK&gE-US3-ST-CD showed a high serum neutralization index against the PRV variant. In conclusion, these results suggested using codon deoptimization to generate innovative live attenuated PRV vaccine candidates.